A Study of Citizenship on Investment Programs: Past, Present and Future, and Survey on Its Acceptance by HNI Clients - Pallathadka, Harikumar (Integrated Journal for Research in Arts and Humanities, 2022)
Following Malta's choice to sell its citizenship in 2013, the request for citizenship by venture (CBI) programs soared. Caribbean legislatures, then again, have been "selling" their citizenship for quite a while, much before Malta. This article unloads the variables that empower the sending of CBI programs and investigates their ability to help financial improvement in a "group of countries" - for example, the five Caribbean nations that run CBI programs utilizing a contextual investigation procedure. It likewise sees how outsiders (like unfamiliar state-run administrations) see residents of CBI-allowing countries, contending that the outer political expenses of speculative double-dealing of these nations' citizenship might offset the financial advantages. Malta was the subject of heated debate in the European Parliament in January 2014. The island state had set up a citizenship-in-exchange-for-business-transactions scheme, intended to be used as an economic policy tool to gather and make ‘money,' with citizenship and hence migration rights as its lure. It is ruling also meant that European citizenship would be bestowed. Both politicians and academics viewed the Maltese citizenship-by-investment program (CIP) as akin to "selling" the EU's primary status, and it was widely panned: Several articles on the subject have brought criticisms such as "programs corrode democracy," "they undermine citizenship," and "CIPs enhance global inequity."